Накопичення важких металів в грунті та зольність листків деревних рослин насаджень міста Львова - Гнатів, П.С.; Коршиков, І.І. (Промышленная ботаника, 2006)
Analysis of soil heavy metal content of different plantations in L’viv (suburban forest park, square, street alleys) and also leave ash content in arboreal urban plants of these stands was conducted. It was fixed that content of molybdenum, barium, lead, silver and copper in soil overlay (0-20 sm) rised from town skirt to its center. On the whole, forest soil was contaminated by heavy metals worst, street alleys soil – most. Increased ash content of leaves was fixed for plants from parks and squares and a shade less for street plantations. It may be connected with the worse mineral amendment conditions of plants.